A Miniaturized In Situ Tensile Platform under Microscope - Zhichao Ma; Hongwei Zhao; Hu Huang; Kaiting Wang; Qinchao Li; Xiaoqin Zhou; Xiaoli Hu (Institute of Advanced Engineering and Science, 2012)
Aiming at the mechanical testing of three-dimensional specimens with feature size of centimeter level, a miniaturized tensile platform, which presents compatibility with scanning electron microscope (SEM) and metallographic microscope, was designed and built. The platform could accurately evaluate the parameters such as elastic modulus, elongation and yield limit, etc. The calibration experiments of load sensor and displacement sensor showed the two kinds of sensors had high linearity. Testing of transmission error and modal parameters showed that the platform presented good following behaviors and separation of resonance region. Comparison tests based on stress-strain curve were carried out between the self-made platform and the commercial tensile instrument (Instron) to verify the feasibility of the platform. Furthermore, the in situ tensile experiment under metallographic microscope was carried out on a kind of manganese steel. DOI: http://dx.doi.org/10.11591/telkomnika.v10i3.613